Al-Quran Perspective Learning Strategy Surah Al-Alaq (96) Verses 1-5 - Mela Ernia Sari; Supardi Ritonga; Sukma Ningsih; Suziana Suziana; Laras Novitasari; Ferry Irawan Saputra (World Journal of Islamic Learning and Teaching, 2024)
Surah Al-'Alaq (96: 1-5) emphasizes the importance of reading and learning as the foundation of education. These verses invite the community to understand that knowledge comes from Allah and must be pursued with good intentions. In the context of learning strategies, this surah highlights the need for integrating spiritual and ethical values ​​in education. Educators are expected to create a learning environment that focuses not only on mastering the material but on character development too. This study aims to explore the relationship between the teachings in Surah Al-'Alaq and effective learning strategies, as well as their implications for student character development. By applying student-centered learning strategies, it is hoped that students' love and understanding of the Koran will increase, thus forming a generation that possesses noble character and is prepared to face future challenges.